2021
DOI: 10.1101/2021.06.15.448622
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multiple RSV strains infecting HEp-2 and A549 cells reveal cell line-dependent differences in resistance to RSV infection

Abstract: Respiratory syncytial virus (RSV) is a leading cause of pediatric acute respiratory infection worldwide. There are currently no approved vaccines or antivirals to combat RSV disease. A few transformed cell lines and two historic strains have been extensively used to study RSV. Here we report a thorough molecular and cell biological characterization of HEp-2 and A549 cells infected with four strains of RSV representing both major subgroups as well as historic and more contemporaneous genotypes -- [RSV/A/Tracy (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…We had previously observed differences in the kinetics of RSV infection by RSV strain and cell type (44), therefore, we speculated that the efficiency of p27 cleavage and the stability of the pre-F conformation may also be RSV strain and cell type dependent. For these studies we used Imaging Flow Cytometry to measure p27, Site Ø and Site II on virus-infected cells; we mitigated the contribution of fluorescence signal from any non-specific intracellular staining using masks to isolate signals to the surface of the cell membrane during data analysis.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…We had previously observed differences in the kinetics of RSV infection by RSV strain and cell type (44), therefore, we speculated that the efficiency of p27 cleavage and the stability of the pre-F conformation may also be RSV strain and cell type dependent. For these studies we used Imaging Flow Cytometry to measure p27, Site Ø and Site II on virus-infected cells; we mitigated the contribution of fluorescence signal from any non-specific intracellular staining using masks to isolate signals to the surface of the cell membrane during data analysis.…”
Section: Resultsmentioning
confidence: 96%
“…These cell lines also differ in their post-translational modification and processing of the F protein, as higher measurable levels of p27 on HEp-2 cells indicated that this cell line was less efficient in cleaving p27 than A549 cells, confirming that HEp-2 and A549 cells elicit different responses to RSV infection. Our previous study demonstrated that HEp-2 cells produce higher cytokine anti-inflammatory responses to RSV infections, while A549 increases the gene expression of antiviral pathways (44). In addition to cell lines, we also demonstrated differences in p27 between RSV strains in RSV/A and RSV/B subgroups.…”
Section: Discussionmentioning
confidence: 99%